Ecotoxicological Studies on the Bioaccumulation of the Heavy metals in the Vellore population,TamilNadu, India - N. Chandrasekaran, R. Vidya (Recent Research in Science and Technology, 2010)
The study was totally aimed to know the extent of bioaccumulation through the plants from the sediments. Total heavy metals concentration (chromium, lead, zinc, nickel and cadmium) were undertaken in the food composites collected from Puliyanthangal village near Ranipet of Vellore district, Tamilnadu, India. There are around 240 tanneries in these areas, besides number ofÃ‚Â ceramic, refractory, boiler auxiliaries plant and chromium chemical factories. Since the ground water was heavily contaminated with heavy metals, studies were carried out to know if there was transfer of heavy metals in the food chain. Drinking water samples, sediment samples as well as food samples wereÃ‚Â collected and analysed for Chromium, Lead, Nickel, Zinc and Cadmium levels. The Environmental risk assessment was undertaken in the foodchain for all the above metals through water, sediment and through the grains and the crops grown in that area. Bioaccumulation factor was calculated with respect to the above parameters and it was concluded that the heavy metals were found to be concentrated through the various levels of food chain but notÃ‚Â biomagnified through the food chain.